2016
DOI: 10.1007/s10554-016-0895-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of experience in echocardiographic identification of location and extent of mitral valve prolapse with 2D and 3D echocardiography

Abstract: also improved the agreement (+12 to +16 %) and Kappa values (+0.14 to +0.21) in all reader groups for the exact description of P2 prolapse. Differences between readers with variable experience in determining the precise localization and extent of the prolapsing posterior MV scallops exist in particular in 2D-TTe analysis. 3D-TOe analysis was extremely fast compared to the 2D analysis methods and showed the best diagnostic accuracy (mainly driven by specificity) with identification of P1 and P3 prolapse still i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…This technique may also be less operator dependent because it does not require the finesse of probe manipulation to delineate MV pathology. Several studies have shown that time to diagnosis was considerably faster and diagnostic accuracy improved with 3D echocardiography, in particular for identification of P1 and P3 prolapse 6)…”
Section: Classification Of MV Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…This technique may also be less operator dependent because it does not require the finesse of probe manipulation to delineate MV pathology. Several studies have shown that time to diagnosis was considerably faster and diagnostic accuracy improved with 3D echocardiography, in particular for identification of P1 and P3 prolapse 6)…”
Section: Classification Of MV Pathologymentioning
confidence: 99%
“…Because the P2 scallop is relatively large, it may be divided into lateral and medial halves (P2L and P2M) or even divided into three parts: centro-lateral (P2CL), central (P2C), and centro-medial (P2CM). The two commissures are usually also composed of small scallops and may be designated as the lateral commissural scallop (CL) and medial commissural scallop (CM) 6). The chordae arising from the anterolateral papillary muscle are attached to CL, A1, P1, A2L, and P2L, whereas those arising from the posteromedial papillary muscle are attached to CM, A3, P3, A2M, and P2M.…”
Section: Introductionmentioning
confidence: 99%
“…• El uso de programas cuantitativos permite diferenciar DM (volumen tejido prolapsado > 1,15 ml) de DFE (< 1,15 ml) y mejorar exactitud diagnóstica y reclasificar PVM de tipo billowing a flail hasta en 15% de casos. • Mayor precisión y reproducibilidad en localización exacta de la lesión y disminución del tiempo diagnóstico (8) .…”
Section: Discussionunclassified
“…With 3D-TEE, the entire MV can be visualized in a single image, making it possible to examine both leaflets from the left atrial (surgical) perspective, and allowing more definitive identification of prolapse of individual scallops and segments. [5455] Furthermore, TEE has been used as the primary imaging modality for guiding the various steps of percutaneous catheter-based edge-to-edge mitral valve repair with a mitral clip. TEE has been shown to be essential for transseptal puncture guidance, optimal clip positioning, and assessment of the severity of MR before and after final deployment of the clip.…”
Section: Noninvasive Imagingmentioning
confidence: 99%